ClasScorer: Towards a Gamified Smart Classroom - Shoukry, Laila; Bedair, Youssef; Elgedawy, Islam (2022 IEEE Global Conference on Artificial Intelligence and Internet of Things (GCAIoT), 2022)
There is a need for continuous monitoring of student engagement and learning to be able not only to assess teaching strategies but also to encourage student competition and participation. Today's smart classrooms offer unprecedented opportunities for advancing multimodal learning analytics and gamifying educational interactions to fit the needs of today's generation. Most research efforts which try to make technology compete with instructors continue to prove that technology, although having many undoubtable benefits for education, is not (yet) ready to replace personal instruction. Smart infrastructure and applications should rather empower instructors and augment students' learning experience seamlessly in naturalistic settings. In this paper, ClasScorer is proposed as an unobtrusive platform for gamifying smart classroom learning interactions to help instructors monitor and encourage student in-class participation. After an analysis of the current state of smart classroom research and user survey results are presented to show the need for this research direction, the proposed architecture and first prototype are described and demonstrated in different use case scenarios.